Nemo Propheta in Patria: Empirical Evidence from Italy - Emanuele Millemaci; Alessandra Patti (Fondazione Eni Enrico Mattei (FEEM), 2022)
In recent years, young brain drain within Italian provinces has increased at higher speed than ever. While is premature to assess whether this process is transitory or permanent, it should be analysed and monitored by researchers and policy makers for its many socio-economic consequences. Previous empirical studies have demonstrated that Italian net skilled migration is influenced by economic factors, such as income per capita and employment, and, with a less extent, by the search of places endowed with more amenities. In the crossroad between these factors, this paper investigates corruption as key element of the Italian skilled mobility. To this end, a comprehensive framework with Zero-Inflated Poisson and Pseudo-Poisson Maximum Likelihood with High Dimensional Fixed Effects models for bilateral data on the Italian students' flows is used. Results suggest the dual role of push and pull mechanisms at play, as high corruption incentivizes Italian skilled mobility to destinations that, instead, exhibit lower corruption. Moreover, sensitivity of the prospective tertiary students to corruption varies according to their field of study of interest. Finally, empirical evidence on skilled flows from the lagging Mezzogiorno to the North of Italy, suggests that the push and pull effects of corruption stir up the endurance of the well-known socio-economic dualism between these two parts of the country.
Keywords: D73; F12; R23; 330; Brain drain; Corruption; Panel data; Gravity; Zip; Ppmlhdfe